Literature among the ruins, 1945-1955 : postwar Japanese literary criticism - Ueda, Atsuko; Bourdaghs, Michael K.; Sakakibara, Richi; Toeda, Hirokazu, 1964- (New studies in modern Japan., 2018)
This collection examines literary criticism in postwar Japan. The contributors analyze the debates that occurred among Japanese intellectuals and highlight the various ideological forces that shaped the country's postwar trajectory.